Development of dual-axis solar tracking using arduino - Abed, Saif Ahmed (2020)
Renewable energy sections are fast-spreading, as they can be considered new growth areas for many countries. Contains many economic and environmental possibilities. As solar energy is considered to have a major and effective role for the acquisition of energy, in the face of the identification of rural areas that are difficult to access electric power. The traditional solar power system used is produces weak energy by assumption that the sun is moving all the day, therefore requires the purchase of more solar panels refer to the high cost .The project aims to develop the traditional solar system to solar tracking system using Arduino, two servo motor and light dependent resistor (LDR) to obtain high efficiency in electric power generation. Where, the main goal agreed is to track the sunlight at its maximum intensity until the panel move towards the sun, and the project is divided into two main parts, the development of software and hardware. In hardware development will be used four LDR installed on plastic base on solar panel, connected wires to transfer the measurements from sensors to Arduino with resistances and Multi-meter to measure the required energy coming from the panel